PENGARUH LITERASI KEUANGAN, TOLERANSI RESIKO DAN PERSEPSI RESIKO TERHADAP KEPUTUSAN INVESTASI CRYPTO CURRENCY DI SULAWESI SELATAN - Khalik, Abdul Khalik; Sultan, Muh.Salim; Hamzah, Mukhtar (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2024)
This research aims to find out and analyze financial literacy, risk tolerance and risk perception. Partially have a positive and significant effect on investment decisions in Crypto Currency South Sulawesi Branch and to find out and analyze financial literacy, risk tolerance and risk perception. Simultaneously have a positive and significant effect on Investment Decisions in Crypto Currency South Sulawesi Branch and to find out and analyze the variables that have a dominant influence on Investment Decisions in Crypto Currency South Sulawesi Branch. The sampling technique uses saturated samples, where the entire population is sampled. The number of samples in this study was 76 respondents. The analytical method used is the Multiple Linear Regression Analysis Method. The research results show that financial literacy, risk tolerance and partial risk perception have a positive and significant effect on investment decisions in the South Sulawesi Branch of Crypto Currency. Financial literacy, risk tolerance and risk perception simultaneously have a positive and significant effect on investment decisions in the South Sulawesi Branch of Crypto Currency. The variable that has a dominant influence on Investment Decisions in Crypto Currency South Sulawesi Branch is financial literacy.